2019
DOI: 10.1152/japplphysiol.00652.2018
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a physiological increase in temperature on mitochondrial fatty acid oxidation in rat myofibers

Abstract: We investigated the effect of temperature increase on mitochondrial fatty acid (FA) and carbohydrate oxidation in the slow-oxidative skeletal muscles (soleus) of rats. We measured mitochondrial respiration at 35°C and 40°C with the physiological substrates pyruvate + 4 mM malate (Pyr) and palmitoyl-CoA (PCoA) + 0.5 mM malate + 2 mM carnitine in permeabilized myofibers under nonphosphorylating ([Formula: see text]) or phosphorylating ([Formula: see text]) conditions. Mitochondrial efficiency was calculated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Sparks et al (2016) showed that training-induced increases in insulin sensitivity were associated with increased FA-induced uncoupling. Nevertheless, such putative training-induced uncoupling for fatty acids was not increased by heat acclimation, as we expected, because of the previously found acute effect of heat on fatty-acid uncoupling (Tardo-Dino et al, 2019). In our study, neither alterations of UCP-3 nor ANT-1 protein expression can explain such a decrease in the RCR.…”
Section: The Mitochondrial Efficiency Quality and Dynamics Observed After Endurance Training Are Not Altered By Heat Acclimationsupporting
confidence: 60%
“…Sparks et al (2016) showed that training-induced increases in insulin sensitivity were associated with increased FA-induced uncoupling. Nevertheless, such putative training-induced uncoupling for fatty acids was not increased by heat acclimation, as we expected, because of the previously found acute effect of heat on fatty-acid uncoupling (Tardo-Dino et al, 2019). In our study, neither alterations of UCP-3 nor ANT-1 protein expression can explain such a decrease in the RCR.…”
Section: The Mitochondrial Efficiency Quality and Dynamics Observed After Endurance Training Are Not Altered By Heat Acclimationsupporting
confidence: 60%
“…We used two protocols to study mitochondrial metabolism. The first was a protocol with three aims: (1) determination of the rate of the maximal oxidative capacity (Vmax), (2) determination of the specific oxidation for pyruvate (V maxPyr ), consisting of the successive addition of 2 mM pyruvate, 0.1 mM ADP, 20 mM creatine, 2 mM ADP, 10 mM glutamate, and 12 mM succinate in the presence of 4 mM malate and (3) estimation of the Km for ADP, with or without creatine, using the Michaelis Menten equation (Kuznetsov and Saks, 1986;Kuznetsov et al, 1996;Anflous et al, 2001;Ponsot et al, 2006;Perry et al, 2012): The second protocol, was used to measure the maximal rates of respiration with Palmitoyl-CoA, a long-chain fatty acid (Ponsot et al, 2005;Tardo-Dino et al, 2019) which must be transported across both mitochondrial membranes (via CPT-1 and CPT-2) in the presence of carnitine. We added Palmitoyl-CoA (final concentration of 400 µM) in the presence of 1 mM carnitine, 2 mM ADP, and 0.5 mM malate.…”
Section: In Situ Study Of Mitochondrial Respirationmentioning
confidence: 99%
“…Notably, the significance between NRS and FRS at the same age exhibited a consistent tendency of higher profiles in NRS, indicating a capability of promoting fatty acids profiles in muscles, which was probably because FRS ducks suffered more from the temperature changes than in NRS. For instance, Tardo-Dino et al. (2019) found the temperature increase lead to less efficient oxidative phosphorylation of fatty acids in the soleus of rats.…”
Section: Discussionmentioning
confidence: 99%